Análise de patologias dos edifícios em Curitiba/ PR - Santos, Lorena Durau Carloto dos (2019)
The useful life of a building can be severely affected by building pathologies, a fact that requires technical monitoring of buildings. This paper aims to analyze the pathologies based on the location of the buildings in which they are located, the types of pathologies evidenced and how often they were verified, as well as the identification of the origin by phase of the work and harmful effects of these manifestations in the case of 86 buildings aged between 01 and 05 years in Curitiba / PR. Through the evaluation of the database of an Engineering Company, the Building Inspection Reports issued were evaluated, and surveys of the reported problems were performed. Considering 03 major classification groups (structure, fences, facilities), it can be observed that the group of fences has the most pathological manifestations, followed by the group of facilities and structure. Also, the origin of the pathologies in most of the cases analyzed was attributed to the phase of use, operation and maintenance of the building; followed by the execution phase and, respectively, the project phase. The most significant harmful effect on buildings has been configured as the security risk.